Contextual Effect of Integrated Health Post, Socioeconomic and Physical and Mental Health Determinants on the Quality of Life among Elderly in Klaten, Central Java - Annisa Nur Fauziyah; RB. Soemanto; Rita Benya Adriani (Journal of Epidemiology and Public Health, 2020)
Background: The increase in life expectancy has an impact on the number of elderly which has increased from 9.3% (2018) to 15.8% (2035). Decreased body function in the elderly disturbs health and inhibits activities so that quality of life decreases. The purpose of this study was to ana